Stability Cogitated Electric Vehicle Charging Infrastructure Planning - C.H. Dharmakeerthi; Mithulananthan Nadarajah (International Journal of Smart Grid and Sustainable Energy Technologies, 2017)
Electrification of the transportation is taking place at an accelerated rate. Even though, electric vehicles (EV) evidently bring numerous environmental and economic benefits, their impact on power systems should not be overlooked. It has been identified that EV load characteristics can significantly affect power system voltage stability and small signal stability. Hence, it is important to consider mitigating of stability impacts right from the planning stage of bulk EV charging stations. However, unavailability of suitable stability evaluating indexes that could fit into planning algorithms is a hindrance. This study proposes two computationally efficient indexes to compare stability status in different planning options. The developed indexes have been tested, verified and utilized in a multi objective planning algorithm to identify a comprehensive solution, which satisfies the grid operator, EV customer and the charging facility investor optimally.